Factors influencing parental pregnancy decision-making due to fetuses with non-syndromic orofacial clefts: a study of Chinese couples - Huanhuan Ding; Weizeng Zheng; Xinfen Xu; Baohua Li (Clinical and Experimental Obstetrics & Gynecology)
Background: When a fetus is diagnosed with facial deformities, most Chinese couples choose to terminate the pregnancy. However, these couples commonly regret their decision after the termination of the pregnancy, display a heavier degree of grief, and these feelings persist for a long time. The purpose of this study was to investigate factors that influence parental pregnancy decisions regarding fetuses diagnosed with a non-syndromic orofacial cleft (NSOFC), and to provide the preliminary basis for a formulation of interview outlines useful in further qualitative research in this area. Methods: We collected medical records of 400 couples from the obstetrical units of a women’s hospital in China whose fetuses were diagnosed with Orofacial clefts (OFCs) from January 2013 to July 2019. After excluding those records reporting chromosomal or other abnormalities, 311 cases were included in this study. After univariate analysis, factors that may have affected the parental pregnancy decision were analyzed using binary classification regression analysis. Results: Among the 311 couples, 71.7% (223/311) decided to terminate the pregnancy, whereas 28.3% (88/311) decided to continue. The registered residence, family history of NSOFC, maternal high-risk factors that may lead to the fetus suffering from NSOFC, maternal age, paternal age, doctor’s suggestion, prenatal diagnosis, and first diagnosed gestational week all influenced pregnancy decision makings (p < 0.05). Among these, the registered residence, family history of NSOFC, maternal high-risk factors, maternal age, prenatal diagnosis, and first diagnosed gestational week substantially affected the parental pregnancy decision. Discussion: The couples with registered residence in rural areas, no family history of NSOFC, no maternal high-risk factors, younger maternal age, younger gestational age at first diagnosis are at greater relative risk of pregnancy termination. Prenatal diagnosis is a protective factor.